ANALISIS NERACA AIR DI KOTA TARAKAN PROVINSI KALIMANTAN UTARA - Sudirman Sirait; Hendris Hendris (FAKULTAS PERTANIAN UNIVERSITAS BORNEO TARAKAN, 2019)
Abstract Water needs for agricultural activities in Tarakan City which are located at the geographical coordinates of 117°34¢-117°38¢ East Longitude and 3°19¢-3°20¢ Nort Latitude are still dependent on rainfall, so that there is potential for uncertainty in water availability for plant. Water is one of the absolute factors needed by the agricultural sector for growth and development of plant that affects crop production. Production of agricultural products will decrease if the plants be through water stress. The water balance analysis method is a method that can know the level of carrying capacity of water resources, especially in water storage capacity for groundwater recharge. This study aims to analyze the water balance in Tarakan City to occupy plant water needs. This research was divided into several stages, which are the literature study, the data collection, and the data analysis. The results showed that during the period of 2008-2017 the Tarakan City area had a reliable rainfall value of 3497.68 mm/year, an average ETp value of 41.65 mm/month, a total CH value of more than 2997.88 mm, runoff value of 1630.34 mm, and groundwater recharge value of 1367.54 mm. Based on the results of the water balance analysis, that the Tarakan City area does not encounter a water deficit so that it can support crop cultivation activities and fulfill crop water needs to increase productivity. Key words: Groundwater Recharge, Rainfall, Run-Off, Water Balance, Water Resources AbstrakKebutuhan air untuk kegiatan pertanian di Kota Tarakan yang terletak pada koordinat geografis 117°34¢-117°38¢ Bujur Timur dan 3°19¢-3°20¢ Lintang Utara masih tergantung pada air hujan, sehingga berpotensi terjadinya ketidakpastian ketersediaan air untuk tanaman. Air merupakan salah satu faktor mutlak yang diperlukan sektor pertanian untuk pertumbuhan dan perkembangan tanaman yang mempengaruhi produksi tanaman. Produksi hasil pertanian akan menurun jika tanaman mengalami cekaman air. Metode analisis neraca air merupakan suatu metode yang dapat mengetahui tingkat daya dukung suatu wilayah terutama daya dukung sumberdaya air untuk kegiatan pertanian sehingga dapat memberikan rekomendasi upaya pengelolaan limpasan dan pengisian air tanah. Penelitian ini bertujuan untuk menganalisis neraca air di Kota Tarakan untuk memenuhi kebutuhan air tanaman. Penelitian ini dibagi dalam beberapa tahapan yaitu studi pustaka, pengumpulan data, dan analisis data. Hasil penelitian menunjukkan bahwa selama periode 2008-2017 wilayah Kota Tarakan memiliki nilai curah hujan andalan 3497,68 mm/tahun, nilai ETp rata-rata 41,65 mm/bulan, total nilai CHlebih 2997,88 mm, nilai limpasan 1630,34 mm, dan nilai pengisian air tanah 1367,54 mm. Berdasarkan hasil analisis neraca air, bahwa wilayah Kota Tarakan tidak mengalami defisit air sehingga dapat mendukung kegiatan budidaya tanaman dan memenuhi kebutuhan air tanaman untuk meningkatkan produktivitas. Kata kunci: Curah Hujan, Limpasan, Neraca Air, Pengisian Air Tanah, Sumberdaya Air